IVERMECTIN IN THE TREATMENT OF COVID-19 DISEASE: A SYSTEMATIC REVIEW AND META-ANALYSIS - LAKSEMI, DEWA AYU AGUS SRI; TUNAS, I. KETUT; WIDYADHARMA, PUTU EKA; ARTAWAN, WAYAN GDE; SUNDARI, LUH PUTU RATNA (International Journal of Applied Pharmaceutics, 2022)
Objective of the review was to evaluate the effectiveness of Ivermectin as a treatment of COVID-19. The researchers collected and assessed articles and previous studies in the form of Randomized Clinical Trial (RCT) from PubMed, Google Scholar, Clinical Trials Gov and Preprint databases. The inclusion criteria of the study were the patients diagnosed with mild to moderate COVID-19 who had only been given Ivermectin compared to placebo or Standard of Cure (SoC) of COVID-19. There are 11 RCT which are resemble to the inclusion criteria of the study. Based on the 11 RCT that are suitable to the inclusion criteria of the study, the researchers found the pooled OP rate for viral load, Day to Negativity (DTN), and Escalation of Cure for all studies are 62% (95% CI, 0.50-0.74), 89% (95% CI, 0.40-1.38) and 43% (95% CI, 0.06-0.08) respectively. Moreover, the pooled OR rate for length of stay or hospitalization, mortality or deterioration, symptom reduction of all studies are 100.6% (95% CI, 0.54-1.58). Due to the lack of substantial data on information sources and low-to-moderate quality of studies which are included in systematic review, the evidence suggests that IVM (Ivermectin) administration does not decrease the mortality, symptom and viral load of COVID-19.